Epidemiology and cost of seasonal influenza in Germany - a claims data analysis - Stefan Scholz; Oliver Damm; Udo Schneider; Bernhard Ultsch; Ole Wichmann; Wolfgang Greiner (BMC, 2019)
Abstract Background Seasonal influenza contributes substantially to the burden of communicable diseases in Europe, especially among paediatric populations and the elderly. The aim of the present study was to estimate the incidence of seasonal influenza in Germany, the probabilities of related complications and the economic burden of influenza per case and on a population level for different age groups. Methods Claims data from 2012 to 2014 from > 8 million insured of a large German sick-ness fund were analysed. A matched case control study was used on a sub-sample of 100,000 influenza cases to calculate complication rates for ear infections/acute otitis media (AOM) and community-acquired pneumonia (CAP) as well as resource use and costs for seven age groups. Results Incidence of seasonal influenza varies between the years and is highest among infants and children 2 to 5 years of age. AOM is more likely in the younger age groups with up to 14% more patients in the influenza group than in the control group. CAP is more frequently observed in the younger age groups and in influenza patients 60 years and older. The manifestation of one influenza complication (AOM or CAP) significantly in-creases the occurrence of a second complication (AOM or CAP). The economic burden per case is highest in infants (€251.91) and persons over 60 years of age (€131.59). Conclusion The burden of influenza is highest among infants and young children, which is also reflected in the economic burden. Influenza related costs per case are nearly double for infants compared to persons over 60 years of age.